(untitled) (Transport systems and technologies, 2019)
Since fuel consumption significantly depends on the vessel‟s speed, operation of vessels at low speeds is widely used in world practice. On the one hand, reducing the speed of vessels allows saving fuel, which helps to reduce the cost of transportation. But, on the other hand, too long cargo delivery time may not always be acceptable for cargo owners. Therefore, studies aimed at choosing an economically viable speed of vessels are particularly relevant. The purpose of the work is to develop measures aimed at improving the operational efficiency of vessels used in tramp shipping, taking into account the possibility of reducing vessels‟ speed, as well as the rationale for choosing an investment project for acquiring and operating vessels using multi-criteria estimates. Studies have shown that when justifying projects for the acquisition and operation of vessels, it is necessary to take into account the speeds in which these vessels are planned to be used. The effectiveness of projects for the acquisition and operation of bulk carrier vessels can be significantly improved by means of the informed choice of the vessels speed. This made it possible to make an informed choice of the investment project for acquiring a bulk vessel and the optimal speed limit for its use, taking into account both the value of economic indicators of the efficiency of use of the vessel and the average time of cargo transportation.